Production characteristics of Angoni cattle in Mozambique: 1. Non-genetic influences on pre-and post-weaning growth - Tomo, P.S.M.; Tawah, C.L.; Swanepoel, F.J.C.; Hoogenboezem, J.M. (1999)
Sex of calf and year of birth significantly affected birth weight and post-weaning growth. Pre-weaning weights, and pre-and post-weaning growth were significantly affected by season of calving. Cow fertility had a significant influence on weaning, 12- and 18-month weights. Although male calves were heavier than females at birth, the latter gained much more wight from weaning to 18 months. Winter calvers produced heavier calves at birth and weaning than summer calvers. Calves born in summer gained much more weight to 18 months than winter calves. Calves from least fertile cows grew more rapidly and were heavier at all ages than those from the average or most fertile cows.